Helikobacter Pylori Bacteria - Nomads Or Sediмent Microorganisms In The Stomach Mucosa? - Eshbekov Muxtor Eshbekovich; Rakhimov Abduraim Fazilovich (Genius Journals, 2024)
In the article, the authors express their personal opinion about the properties of the bacterium Helikobacter pylori. As a result of studying the interaction of the urease enzyme with gastric juice, was revealed a sharp decrease in the concentration of the free hydrochloric acid fraction in the studied objects. Based on this, contrary to the accumulated facts in the world literature about the cause-and-effect relationship between Helikobacter pylori bacteria and peptic ulcer disease, they claim the opposite - about the usefulness of the mentioned bacteria. The facts they presented about the physical and biological properties of ammonia are of some interest. Their philosophical reflections on the nature of the processes that provide the human body with nutrition are worthy of attention.
Keywords: Peptic ulcer; gastric juice; urease